Without a conflict model of electron - Tchaban, Vasil (Вопросы атомной науки и техники, 2019)
The model of electron is oﬀered with quark distribution of charge density and ”white hole” (on similarity of ”black hole” in gravitation) in a center. Such structure abolishes the crisis of electromagnetic mass, calculated on universal formula and on the impulse of the electromagnetic ﬁeld. A model in order to please a classic electrodynamics keeps monolithic nature of elementary particle, and in order to please a quantum allows the separate charged zones to interpret as separate quarks. Coming from harmony of spheres of the separate charged zones, a white hole can be interpreted as white (neutral) quark conditionally in addition to three coloured. As after the electric radius re = 1.185246·10⁻¹⁵ m of white hole the laws of electricity do not operate, then the crisis of point charge is removed at the same time too, because of must be: r ≥ re.